Effects of an Intervention Focused on Child Emotion Socialization - Lins, Taiane Costa de Souza (2023)
Punishing, minimizing, ignoring, or becoming distressed when dealing with children’s negative emotions may favor the emergence or worsen behavior problems during childhood. This study examined the effects of the intervention program Vivendo Emoções [Experiencing Emotions] on maternal reactions to children’s emotions and children’s internalizing and externalizing problems. Thirty-two mothers of children aged between three and eight participated and were assigned to an intervention (n = 16) or a comparison (n = 16) group. The intervention was implemented in eight sessions intended to promote the mothers’ strategies to identify and regulate their children’s negative emotions and enable the children to improve emotional competence. The mothers completed the CCNES to report their reactions to children’s emotional expressions and the CBCL to report internalizing and externalizing problems on pretest and posttest. The results reveal that mothers in the intervention group reported fewer unsupportive reactions on posttest than mothers in the comparison group. This finding shows the potential of such interventions to decrease unsupportive maternal reactions. Additionally, children in the intervention group presented more frequent somatic complaints than those in the comparison group on posttest. A potential explanation is that the mothers were more prepared to encourage their children to report negative emotions associated with bodily sensations.